Thermal Pyranometer Using the Open Hardware Arduino Platform - Avallone, Elson [UNESP]; Mioralli, Paulo Cesar [UNESP]; Scalon, Vicente Luiz [UNESP]; Padilha, Alcides [UNESP]; Oliveira, Santiago del Rio [UNESP] (Int Center Applied Thermodynamics, 2018)
Thermal Pyranometers are very important devices for evaluating the intensity of solar radiation under different climatic conditions. These devices utilize thermal radiation for comparison and determination of their efficiency. Because of this wide use associated with the development of new technologies, a simple and low-cost version of thermal pyranometer has been studied, designed and manufactured. A blackened aluminum disk is used as a hot junction, and the cold junction is exposed to ambient air. The two terminals are connected to a digital amplifier with output signal directed to an Arduino board. A device calibration was performed by comparing the results with a commercial photodiode sensor. Statistical analysis of the calibration data considering a 99% confidence level leads to an estimated standard error of 20.8 W/m(2). An analysis of its response time also estimated from a dynamic model. This model uses a numerical solution of the energy balance on heat exchange between the aluminum disc and the environment. The instrument response time based on the average of the estimates obtained from the dynamic model is about 1.5 minutes. Based on these studies it was concluded that the characteristics of the sensor are adequate for most solar energy tests and the final cost of US $ 60.00 is much lower than the large majority of such commercial devices.
Keywords: Pyranometer; Radiometer; Thermal sensor; Arduino